Cyber-Attacks in Accordance with International Humanitarian Law - Daraji, Mohammad Hasan; AL-Okour, Omar Saleh (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to demonstrate the applicability of the rules of international humanitarian law to cyber-attacks, as international humanitarian law aims to regulate the exceptional right to use force to resolve disputes, as such use of force is internationally prohibited under the UN Charter. Methods: Two approaches were employed in this research. The first is a descriptive-analytical approach, which starts from the description of the phenomenon under question, the legal approach that is taught in political and international system institutions, and the relationship between them. The second is a historical approach, which traces the historical events surrounding the emergence of the term ‘cyber-attacks’. Results: There are two different approaches regarding the issue of the subordination or non-subordination of cyber-attacks to the provisions of international law, the most likely approach is that cyber-attacks are subject to the provisions of international law. This approach is encouraged so as to avoid falling into the problem of evasion of international responsibility which could then lead to committing more massacres against civilians as a result of the use of cyber-attacks as a weapon. Conclusions: The study recommends the necessity of adapting the rules of international humanitarian law to align with the unique nature of cyber attacks and applying them as weapons and methods of warfare in armed conflicts. Efforts should continue to amend these legal rules to achieve explicit international legal regulation for cyber attacks.